IMPLEMENTATION OF THE TRANSIT-ORIENTED DEVELOPMENT (TOD) CONCEPT AT HARMONI BUSWAY STOP - Herika Muhamad Taki; Hanuum Salsabila; Zefanya Elsyeria Yonathan; Astari Minarti (Journal of Synergy Landscape, 2025)
Urban issues such as limited land, traffic congestion, and air pollution in Jakarta require efficient solutions. Transit-Oriented Development (TOD) is a concept aimed at maximizing land use and improving public facilities around transit hubs. This research evaluates the implementation of the TOD concept at the Harmoni Busway Station in Central Jakarta using QGIS software to assess data conformity with TOD principles. The results show that the Harmoni Busway Stop meets most TOD principles, mainly walking, cycling, and connecting, with sufficient sidewalks, bicycle lanes, and intermodal connections. However, further development is needed in mix-use and eco-friendly facilities to optimize the area's function as a sustainable transit hub.